Synthesis, biological evaluation and molecular dynamic simulations of novel Benzofuran-tetrazole derivatives as potential agents against Alzheimer's disease. Issue 1 (1st January 2019) - Kushwaha, Pragati; Fatima, Soobiya; Upadhyay, Akanksha; Gupta, Sampa; Bhagwati, Sudha; Baghel, Tanvi; Siddiqi, M.I.; Nazir, Aamir; Sashidhara, Koneni V.
Graphical abstract: Highlights: A series of benzofuran-tetrazole derivatives were synthesized as potent AChE inhibitors. Several compounds exhibited significant neuroprotective and A β aggregation inhibitory activities. Docking studies corroborated well with the anticholinesterase assay results. Abstract: A series of novel Benzofuran-tetrazole derivatives were successfully synthesised by integrating multicomponent Ugi-azide reaction with the molecular hybridization approach. Interestingly, a number of synthesized derivatives (5c, 5d, 5i, 5l, 5q and5s ) exhibited significant reduction of aggregation of "human" amyloid beta peptide, expressing on transgenic Caenorhabditis elegans ( C. elegans ) strain CL4176. Further, in silico docking results have evidenced the exquisite interaction of active compounds with the help of TcAChE–E2020 complex. These findings underscore the potential of these hybrids as lead molecules against Alzheimers's disease.